Prolonged Amenorrhea and Low Hip Bone Mineral Density in Women Living With HIV—A Controlled Cross-sectional Study. (15th April 2020) - King, Elizabeth M.; Nesbitt, Ariel; Albert, Arianne Y.K.; Pick, Neora; Cote, Helene C.F.; Maan, Evelyn J.; Prior, Jerilynn C.; Murray, Melanie C.M.
Abstract : Background: Women living with HIV (WLWH) have higher rates of prolonged secondary amenorrhea (no flow for ≥1 year) than HIV-negative women. Both having amenorrhea and being HIV positive are associated with lower areal bone mineral density (BMD). However, their combined BMD effects remain unclear. Therefore, we investigated prolonged amenorrhea and BMD in WLWH and controls. Methods: This cross-sectional study enrolled WLWH and HIV-negative control women aged 19–68 years of similar backgrounds. We assessed BMD (Hologic; as age- and ethnicity-matched Z-scores) in the Children and women: AntiRetrovirals and Markers of Aging cohort. Participants were stratified by amenorrhea history defined as past/present lack of menses for ≥1 year at age 45 and younger and not because of surgery, breastfeeding, pregnancy, or hormonal contraception. Hip and spine Z-scores by amenorrhea/no amenorrhea used linear models with multivariable analysis for relationships within WLWH. Results: WLWH (N = 129) were similar to controls (N = 129) in age, body mass index, ethnicity, and substance use. Among WLWH, 21% experienced prolonged amenorrhea vs. 9% in controls. WLWH had significantly lower total hip (mean ± SD: −0.4 ± 0.9 vs. 0.3 ± 1.1; P < 0.001) and spine (−0.5 ± 1.3 vs. 0.2 ± 1.3; P = 0.001) Z-scores than controls. Amenorrhea was independently associated with hip ( P = 0.01) but not spine ( P = 0.94) BMD by multivariable linear regression. WLWH with amenorrhea had lower hip Z-scores (−0.8 ± 0.9) than those without (−0.3 ± 0.8; P = 0.01). They also had higher rates of substance use, smoking, opioid therapy, hepatitis C coinfection, and lower CD4 nadir. Conclusions: WLWH had higher rates of prolonged amenorrhea and lower BMD than controls. WLWH with amenorrhea experienced lower hip BMD Z-scores than those without. Prolonged amenorrhea is an added osteoporosis risk in WLWH. Abstract : Supplemental Digital Content is Available in the Text.